Characterisation of a new flat mechanical shear connection mean for steel-concrete composite columns. (October 2019) - Odenbreit, C.; Chrzanowski, M.; Obiala, R.; Bogdan, T.; Degée, H.
Abstract: For buildings in steel-concrete composite structure, the current practice of the shear connection in fully embedded columns is the implementation of headed shear studs. This type of connector has been mainly developed for composite beams and some disadvantages have been identified for column application. For example, due to the shear stud geometry, the difficulty of the reinforcement application and more complicated handling of the column are recognised. Taking into account the additional high resistance, stiffness, ductility and production efficiency criteria, an innovative type of flat shear connection, with the potential for a fully automatic fabrication process has been developed. The proposed new type of shear connectors is made out of regular reinforcement bars welded to the flanges of steel profiles under a specific arrangement. The conducted investigation consisted of three different variants: transversal, longitudinal and angled (V-shaped) of connectors applied to the HEB120 steel profiles. In addition, tests without any mechanical connectors were conducted as reference tests. The specific load-bearing behaviour in terms of load-slip curves for each connector variant has been obtained and analysed. After the tests, the specimens were opened and the failure patterns were investigated. 3D non-linear numerical simulations in the FE code Abaqus® have supported the performed investigations. In the results, the load flux, the decisive force-transfer mechanisms and resistance limits have been identified.